Modulation of amyloid fibrillation of bovine β-lactoglobulin by selective methionine oxidation. Issue 19 (17th March 2021) - Maity, Sanhita; Sepay, Nayim; Pal, Sampa; Sardar, Subrata; Parvej, Hasan; Pal, Swarnali; Chakraborty, Jishnu; Pradhan, Anirban; Halder, Umesh Chandra
Abstract : This work reports selective methionine oxidation of β-lactoglobulin by t BHP reduces its thermal stability and enhances fibrillation propensity. Abstract : Deposition of oxidation-modified proteins during normal aging and oxidative stress are directly associated with systemic amyloidoses. Methionine (Met) is believed to be one of the most readily oxidisable amino acid residues of protein. Bovine beta-lactoglobulin (β-lg), a model globular whey protein, has been presented as a subsequent paradigm for studies on protein aggregation and amyloid formation. Herein, we investigated the effect of t -butyl hydroperoxide ( t BHP)-induced oxidation on structure, compactness and fibrillation propensity of β-lg at physiological pH. Notably, whey protein modification, specifically Met residues, plays an important role in the dairy industry during milk processing and lowering nutritional value and ultimately affecting their technological properties. Several bio-physical studies revealed enhanced structural flexibility and aggregation propensity of oxidised β-lg in a temperature dependent manner. A molecular docking study is used to predict possible interactions with t BHP and infers selective oxidation of methionine residues at 7, 24 and 107 positions. From our studies, it can be corroborated that specific orientations of Met residues directs the formation of a partially unfolded state susceptible to fibrillation with possible different cytotoxic effects. Our studies have greater implications in deciphering the underlying mechanism of different whey proteins encountering oxidative stress. Our findings are also important to elucidate the understanding of oxidation induced amyloid fibrillation of protein which may constitute a new route to pave the way for a modulatory role of oxidatively stressed proteins in neurological disorders.